2011
DOI: 10.1371/journal.pone.0014489
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Recovery of Fat Mass in Small for Gestational Age Preterm Infants after Term

Abstract: BackgroundPreterm small for gestational age (SGA) infants may be at risk for increased adiposity, especially when experiencing rapid postnatal weight gain. Data on the dynamic features of body weight and fat mass (FM) gain that occurs early in life is scarce. We investigated the postnatal weight and FM gain during the first five months after term in a cohort of preterm infants.Methodology/Principal FindingsChanges in growth parameters and FM were prospectively monitored in 195 infants with birth weight ≤1500 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 36 publications
4
58
0
1
Order By: Relevance
“…As the aforementioned results indicate, precision of the ADP system was excellent, with a mean difference of 0.15% between repeated ADP tests. Similarly, there was good agreement between ADP and the H 2 18 O dilution method, as indicated by a mean difference of 0.32% FM and 95% limit of agreement at −3.4 and 2.76 %FM. In addition, regression Articles Air-displacement plethysmography analyses with the two methods provided a low SEE value of 1.65% and a moderate R 2 value of 0.62.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…As the aforementioned results indicate, precision of the ADP system was excellent, with a mean difference of 0.15% between repeated ADP tests. Similarly, there was good agreement between ADP and the H 2 18 O dilution method, as indicated by a mean difference of 0.32% FM and 95% limit of agreement at −3.4 and 2.76 %FM. In addition, regression Articles Air-displacement plethysmography analyses with the two methods provided a low SEE value of 1.65% and a moderate R 2 value of 0.62.…”
Section: Discussionmentioning
confidence: 71%
“…The differences between the values obtained with the ADP system and the H 2 18 O dilution measurement were not a function of the mean values for the two methods (P = 0.16), indicating no systematic bias as body fatness increased. The 95% limits of agreement were at -3.4 and 2.76 %FM.…”
Section: Air-displacement Plethysmographymentioning
confidence: 86%
See 1 more Smart Citation
“…It has been found that extremely preterm infants, including those born small for gestational age, show a major deposition of fat mass in early postnatal life so that they show an increased adiposity at term-corrected age (7,14). However, within the first 3-4 mo of corrected age, extremely preterm infants succeed in achieving fat mass values similar to those of full-term infants (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, extremely preterm infants, assessed at term-corrected age, have been found to be at increased risk for developing increased and/or aberrant adiposity, which is a known risk marker for cardiovascular disease (7,8). However, it has been reported that preterm infants born appropriate for gestational age succeed in recovering growth and fat mass within the third month of corrected age (9). To our knowledge, data regarding the early dynamic features of growth and body composition changes of late preterm infants are scarce.…”
mentioning
confidence: 99%